Design and Implementation of a Back to Back Interlinking Converter for Ac-Dc Microgrid Applications - Espina-Gonzalez, E; Diaz-Diaz, M; Uriarte-Gonzalez, M; Aravena-Carrasco, J; Ibaceta-Valenzuela, E (Institute of Electrical and Electronics Engineers Inc., 2021)
Alternating Current (AC) and Direct Current (DC) Microgrids have received attention in the last years because they allow the connection of AC and DC resources such as wind and solar energy. The AC and DC stages are connected through interlinking converters which manage the power transference among both sub-microgrids. This paper describes the design and implementation of an AC-DC back-to-back interlinking converter developed for laboratory applications. First, the design of the power stage of the converter is described. Additionally, a conventional synchronous frame control strategy is presented and implemented in a real-time controller. Finally, experimental results are presented to validate the correct operation of the proposed converter to perform AC-DC conversion. © 2021 IEEE.